Influence of Environmental Factors on Handloom Machine Workstation - Mahantare, Yogesh; Thakre, G.V (International Journal of Engineering and Management Research, 2026)
Handloom micro-enterprises often operate in environments characterized by high noise, fluctuating humidity and temperature, poor lighting, and insufficient ventilation—factors known to impact both weaver health and productivity. This paper investigates the influence of these environmental variables on handloom workstation performance and explores optimization strategies including dimensional analysis for scalable process improvements. In this paper, focus is to examine, how humidity control enhances fabric tensile strength; how temperature and air quality influence weaver fatigue; and how ergonomic and environmental modifications can reduce musculoskeletal disorders. Through a structured framework, the study outlines how integrating environmental controls with lean and experimental techniques can elevate productivity, quality, and worker well-being in resource-constrained handloom operations.